2018
DOI: 10.4236/ojml.2018.86018
|View full text |Cite
|
Sign up to set email alerts
|

Laughter as Responses to Different Actions in L2 Oral Proficiency Interview

Abstract: Laughter, as an important interactional resource, has been recognized as not simply a response to humor in many researches. It is much related to an action formation from the perspective of Conversation Analysis. In this oral proficiency interviews for admission into a certain English college between native interviewer and Chinese candidates, there appear quite a number of cases in which laughter serves as the major constituent of the responding turn to the first pair part (FPP) (except for questions) in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Apart from that, laughter is also identified as full of functions in reflecting roles and relations of participants. For instance, Glenn (2010) proposes that in institutional setting, the asymmetries of laughter from interviewer and interviewee could disclose the hegemony of the their roles, which is consistent with doctor-patient interactions (Haakana, 2001;2002), and Gao & Wu (2018) identifies the use of single laughter doing alignment and affiliation in response to prior actions when participants are not competent enough in L2 testing context, which not only shed lights to Chinese candidates' linguistic competence, but reflects their tendency to build relational solidarity. Potter and Hepburn (2010) also regards laughter, in terms of IPA (interpolated particles of aspiration), as the devise to signal "possible trouble in the use of the word or there is more going on than the mere use of the word would indicate" and IPA can be "inserted into lexical items within turns to fitness or modulate the action that is produced in some way".…”
Section: Laughtermentioning
confidence: 84%
See 1 more Smart Citation
“…Apart from that, laughter is also identified as full of functions in reflecting roles and relations of participants. For instance, Glenn (2010) proposes that in institutional setting, the asymmetries of laughter from interviewer and interviewee could disclose the hegemony of the their roles, which is consistent with doctor-patient interactions (Haakana, 2001;2002), and Gao & Wu (2018) identifies the use of single laughter doing alignment and affiliation in response to prior actions when participants are not competent enough in L2 testing context, which not only shed lights to Chinese candidates' linguistic competence, but reflects their tendency to build relational solidarity. Potter and Hepburn (2010) also regards laughter, in terms of IPA (interpolated particles of aspiration), as the devise to signal "possible trouble in the use of the word or there is more going on than the mere use of the word would indicate" and IPA can be "inserted into lexical items within turns to fitness or modulate the action that is produced in some way".…”
Section: Laughtermentioning
confidence: 84%
“…It is regarded as a mark of their delicacy and the device to deal with delicate moments. Delicacy could involve the patients' reluctance to tell their situations or disagreement with doctors' utterance (Haakana, 2001;2002) and aphasic speaker's incompetence (Wilkinson, 2007), children' unwilling or incompetent to parents' speaking (Walker, 2017), and interviewees' nervousness in self-directed assessing and knowing, self-boasting, managing insufficient answer (Glenn, 2013a) and their handling the conflict of avoiding self-praise and offering preferred response when complimenting (Gao & Wu, 2018). Goffman (1956) once describes the "hollow laugh" as one method of trying to conceal embarrassment, and Adelsward (1989), suggests that "embarrassed laughter" can be an attempt to save face.…”
Section: Laughtermentioning
confidence: 99%
“…Language learners use laughter as a 'trouble management device' during uncertainty (Looney and He, 2021), when pre-empting a problematic action (Petitjean and González-Martínez, 2015) and after making an error (Gao and Wu, 2018). In an analysis of UK university English proficiency interviews of 23 Chinese students, Gao (2020) found that laughter co-occurs with disfluencies in three ways: (i), on its own between the reparandum and repair phrase, (ii), alongside indicators of an interruption point such as pauses and word cutoffs, and (iii), simultaneously as laughed speech either during the repair phrase or the whole disfluency.…”
Section: Silence and Laughtermentioning
confidence: 99%